Strategi Peningkatan Traffic Media Sosial Instagram Sebagai Media Promosi Dengan Menggunakan Epic Model Dan Social Media Optimization (Studi Kasus : UKM Buketby.06) - Indriartiningtias, Retno; Waridah, Amnauw; Jannah Suroso, Eka Nur; Amiren, Fuad; Alan Abdullah, Iqbal (Metris: Jurnal Sains dan Teknologi, 2025)
This research aims to increase social media traffic on Instagram of Buketby.06 by applying the Social Media Optimization (SMO) and the EPIC (Empathy, Persuasion, Impact, Communication) model. Buketby.06, an MSME engaged in the production of flower bouquets, faces challenges in increasing social media reach and interaction which impacts sales. Using the EPIC model, promotional effectiveness is analyzed through four main dimensions: empathy, persuasion, impact, and communication. This research also utilizes the SMO method to optimize the content and visual strategy of the Buketby.06 Instagram account. The research results show that the persuasion dimension has the greatest influence on increasing social media traffic, with the highest average score of 3.72. Implementing SMO, including optimizing visual content, using relevant hashtags, and interactive captions, has significantly increased user engagement. Instagram insights before and after improvements show increased engagement (37%), including the number of likes, comments, and shares. The designed strategy not only increases Buketby.06's visibility but also strengthens brand identity through content that is interesting and in line with audience preferences. This research concludes that the combination of the EPIC and SMO models is an effective approach to overcoming social media traffic problems in MSMEs. It is hoped that consistent and data-based strategy implementation will provide long-term benefits for Buketby.06's business development.